2018
DOI: 10.1007/s00449-018-1950-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fundamental nutrient stresses on the lipid accumulation profiles in two diatom species Thalassiosira weissflogii and Chaetoceros muelleri

Abstract: Microalgae are considered as attractive feedstocks for biofuel production nowadays because of their high lipid contents and easy cultivation. In the present study, two diatoms, Thalassiosira weissflogii and Chaetoceros muelleri, were cultured under various nutrient-limitation conditions to explore their comprehensive lipid accumulation profiles for further commercialization. In T. weissflogii, the highest neutral lipid accumulation and highest lipid productivity (14.28 mg L day) were both recorded under P-limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…The highest total lipid content was observed in culture with the lowest concentration of P (7 µM), and it was observed that the total lipid content decreased as the P concentration increased. It has been widely documented in several species of microalgae that under phosphate deficiency, accumulation of neutral lipids is a common response and it has been observed that phospholipid levels in cells are reduced and being repla- Lin et al (2018) are higher than those reported in this study, it is worth to mention that the laboratory's conditions vary among them, as well as the experimental design, the culture media, and the strains; these factors could influence in the final results. On the other hand, although the protein content was higher in culture with the lowest concentration of P (7 µM), no significant differences were found among treatments, but we did find differences between the treatments of P starvation (7 and 18 µM).…”
mentioning
confidence: 59%
“…The highest total lipid content was observed in culture with the lowest concentration of P (7 µM), and it was observed that the total lipid content decreased as the P concentration increased. It has been widely documented in several species of microalgae that under phosphate deficiency, accumulation of neutral lipids is a common response and it has been observed that phospholipid levels in cells are reduced and being repla- Lin et al (2018) are higher than those reported in this study, it is worth to mention that the laboratory's conditions vary among them, as well as the experimental design, the culture media, and the strains; these factors could influence in the final results. On the other hand, although the protein content was higher in culture with the lowest concentration of P (7 µM), no significant differences were found among treatments, but we did find differences between the treatments of P starvation (7 and 18 µM).…”
mentioning
confidence: 59%
“…Lipid bodies (LBs) are produced under different stress conditions like nutrient depletion, high light, metal contamination etc. (d'Ippolito et al, 2015;Lin et al, 2018). In the present study, we made an effort to study the number of LBs and their size in most commonly occurring diatoms species during initial and final growth phases using microscopic analysis (Table 2).…”
Section: Lipid Contentmentioning
confidence: 99%
“…Increase in lipid accumulation after nitrogen starvation has been observed in some diatom species, such as Phaeodactylum tricornutum, Chaetoceros muelleri, and Thalassiosira weissflogii [16,17]. Other nutrient limitation stresses involved in an increased lipid accumulation are phosphorous and silicon deprivation [17,18]. In Chaetoceros gracilis, a combined mild Biology 2020, 9, 5 2 of 17 deprivation of both silicon and sodium chloride produced a lipid accumulation reaching up to 73% of the total cell dry weight [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies show that lipids can accumulate in diatoms after mild or acute nutrient deprivation, generally at the expense of a decrease in biomass [14,15]. Increase in lipid accumulation after nitrogen starvation has been observed in some diatom species, such as Phaeodactylum tricornutum, Chaetoceros muelleri, and Thalassiosira weissflogii [16,17]. Other nutrient limitation stresses involved in an increased lipid accumulation are phosphorous and silicon deprivation [17,18].…”
Section: Introductionmentioning
confidence: 99%